Television Drama in Spain and Latin America : Genre and Format Translation - Julian Smith, Paul (Institute of Modern Languages Research, 2020)
Television Drama in Spain and Latin America addresses two major topics within current cultural, media, and television studies: the question of fictional genres and that of transnational circulation. While much research has been carried out on both TV formats and remakes in the English-speaking world, almost nothing has been published on the huge and dynamic Spanish-speaking sector. This book discusses and analyses series since 2000 from Spain (in both Spanish and Catalan), Mexico, Venezuela, and (to a lesser extent) the US, employing both empirical research on production and distribution and textual analysis of content. The three genres examined are horror, biographical series, and sports-themed dramas; the three examples of format remakes are of a period mystery (Spain, Mexico), a romantic comedy (Venezuela, US), and a historical epic (Catalonia, Spain). Paul Julian Smith is Distinguished Professor at the Graduate Center, City University of New York. He was previously Professor of Spanish at the University of Cambridge. He is the author of twenty books and one hundred academic articles.
Accepted: 2022-06-02T04:31:38Z Journal Abbreviation: Genre and Format Translation
Keywords: 1-TV; 2-Analyses formalistes; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Espagne (corpus analysé); Mexique (corpus analysé); Venezuela (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Debating Women’s Issues on Turkish Television: Exploring the Role of Political Power in Women’s Talk - Özcan, Esra (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
In this contribution, I provide an in-depth rhetorical and textual analysis of a television debate program broadcast in 2015 on the mainstream television news channel, Habertürk TV in Turkey. The debate brought together women committed to varying political projects, including Kemalism, Islamism, leftist movements, Kurdish women’s movements, and feminism. I find this debate program unique because it took place at a crucial moment in Turkey’s recent history, preceding increasing restrictions on the media that eventually cost more than half of the program participants’ jobs and positions. In my analysis, I focus on how the program’s moderator and the women participants define “women’s issues” in an increasingly authoritarian and conflictual political climate where women are divided with regard to supporting or opposing the Justice and Development Party’s (Adalet ve Kalkınma Partisi—AKP) political program. The results of my analysis show that “sisterhood” does not provide common ground for women in a politically polarized environment and women with more political power dominate the conservation.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; Turquie (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Introduction: Turkey’s National Television in Transnational Context - Kaptan, Yeşim; Algan, Ece (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
The Turkish television industry has undergone great transformation during the past three decades and enjoyed unprecedented success among national and transnational audiences alike. This chapter reconsiders the rise of Turkish television as a global player and an emerging national industry from a new theoretical perspective by situating Turkish television within the contemporary global developments of international television markets and within its own national history, economic, political, and cultural dynamics. By providing different examples of key turning points in its history, we offer a brief overview of TV production, distribution, and reception in Turkey since the beginning of the industry. We also illustrate how societal debates around television content, such as Turkish TV dramas (dizis), have ignited the question of representation and caused a struggle over official narratives, resulting in the entwining of the industry and production processes with politics. In our introductory chapter, we argue that with the increasing demand for content and the expansion of access to online TV platforms, emerging TV industries play an intricate and complex role in reshaping global television flows. Therefore, the case of the Turkish TV industry constitutes a significant example for understanding the current structural transformations in global television and sheds light on the interplay between national and transnational production, distribution, and reception processes.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; Turquie (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

‘Calling Out Around the World’: The Global Appeal of Reality Dance Formats - Heller, Dana (Global Television Formats: Understanding Television Across Borders, 2012)
In this chapter, I would like to consider how interactive reality television contributes to the negotiation between national particulars and transnational media ﬂows. Speciﬁcally, I want to look at the successful franchise So You Think You Can Dance , a dynamic global media ﬂashpoint and a remarkably adaptable format that serves as a site of pleasurable and contradictory engagement with the sense of national culture and community that television manufactures. But what makes the show of particular interest to me is that it allows audiences, in an increasing number of television markets around the world, to collectively determine their ideal national performers through a competition that requires mastery of a virtual international smorgasbord of popular dance forms and styles, the vast majority of which originate elsewhere, or from within the national, racial, and ethnic cultures of others. Second, in choosing to examine dance shows, I join with a growing number of scholars who have, over the past 15 years, argued for increased attention to dance as a primary site of knowledge production concerning bodies, identities, and representation.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; Israël (corpus analysé); Proche-Orient (corpus analysé); Turquie (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

McTV: Understanding the Global Popularity of Television Formats - Waisbord, Silvio (Television & New Media, 2004)
Globalization has intensified interconnectivity among television industries worldwide. Interconnectivity happens through structural and institutional linkages among television systems and industries worldwide, resulting in an increasingly integrated global business governed by similar practices and goals. The dynamics are reflected in the popularity of television formats. On the surface, global dissemination of formats may suggest not only the global integration of the economy of the industry but also the standardization of content. A dozen media companies are able to do business worldwide by selling the same idea, and audiences seem to be watching national variations of the same show. At a deeper level, however, formats attest to the fact that television still remains tied to local and national cultures. Bringing up examples of Latin American cases, this article argues that television is simultaneously global and national, shaped by the globalization of media economics and the pull of local and national cultures.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; Argentine (corpus analysé); Brésil (corpus analysé); Mexique (corpus analysé); Royaume-Uni (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Ciné-parcours dans l'Europe contemporaine : routes nécessaires, routes symboliques - Gandolfi, Paola (Cinémas : Revue d'études cinématographiques = Journal of Film Studies, 2010)
Cette vidéaste regarde - et nous fait regarder - la frontière comme un espace mental et matériel : les interviews, la voix over dont le texte apparaît à l'écran, les citations de textes, les images, les sons et le found footage sont combinés de façon à donner un aperçu saisissant et intime à la fois des conditions de vie des femmes (division du travail, prostitution, violence à l'égard des femmes dans les rues, etc.) propres aux régions frontalières, c'est-à-dire se définissant en fonction des contraintes liées à leur position limitrophe, mais offrant une certaine liberté aux gens qui y vivent du fait, justement, de cette position. Il est intéressant de voir comment le road movie permet de réaffirmer la place de l'automobile comme pur moyen de mobilité, mais en même temps comment il nous oblige à nous concentrer sur un autre type de mobilité, que Walter Moser (2008, p. 9) appelle la « médiamotion », soit : une forme de mobilité que nous procurent les médias mais qui, dans un certain sens, remplace ou redouble le déplacement physique en offrant aux êtres humains une expérience presque paradoxale : le contact à distance. On peut également voir dans le road movie contemporain un « road movie interculturel6», parce que la route y trace «un espace imaginaire particulièrement apte à figurer la complexité et les asymétries de l'interculturel » (Gin 2008, p. 41), mais également parce que : l'intetculturalité [...] du road movie résiderait en ce sens dans le mouvement que subit un principe ou une pulsion d'identification culturelle ne pouvant ni se réaliser ou s'assouvir - narrativement, visuellement - dans l'univocité d'un arrêt sur image, ni pour autant s'épuiser on the road Xp. 44). En fait, la mobilité transnationale se situant au centre de cette production filmique «accentuée» donne lieu à un ensemble de tentatives en constante évolution, où les identités culturelles en devenir peuvent être «constamment reformulées dans une perspective future, bien que conditionnées par des liens historiques et des devoirs avec le passé» (Grillo, Riccio et Salih 2000, p. 16), aussi bien que par les liens qu'entretiennent les migrants et les exilés avec leur identité et leur culture d'origine.
Num Pages: 23 Place: Montréal
Keywords: 1-Cinéma; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

All About Almodóvar’s Men - Rey, Juan; Uceda Pérez, Francisco (Peter Lang Inc., International Academic Publishers, 2017)
Pedro Almodóvar is an internationally acclaimed Spanish director. The national and international fascination over Almodóvar's cinema lies in his ability to reflect the problems of contemporary society, his lucidity in combining the urban and the rural, his ability to express the frustrations of modern man, as well as his freshness and spontaneity. Although the vast majority of studies on this Spanish director have focused on women and the gay world, his films are crowded with many types and archetypes of heterosexual men. This groundbreaking edited volume studies the men in the cinema of Almodóvar from a broad yet comprehensive and complementary perspective. Each chapter of All About Almodóvar's Men methodically dissects these male characters—their misery and their greatness, their frustrations and their desires—offering a kaleidoscopic view of man that goes beyond the narrow framework in which many studies have locked the rich cinema of Almodóvar.
Issue: vol. 8
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Identités diasporiques; _Nettoyé

Race-ing Art History: Critical Readings in Reace and Art History - Pinder, Kymberly N (Routledge, 2002)
This comprehensive anthology places issues of racial representation squarely on the canvas. Within these pages are representations of Nubians in ancient art, the great tradition of Westernmasters such as Manet and Picasso and contemporary work by lesser known artists.
OCLC: 804390860
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé

The Routledge Companion to Media and Race - Campbell, Christopher (Routledge, 2017)
"The Routledge Companion to Media and Race serves as a comprehensive guide for scholars, students, and media professionals who seek to understand the key debates about the impact of media messages on racial attitudes and understanding. Broad in scope and richly presented from a diversity of perspectives, the book is divided into three sections: first, it summarizes the theoretical approaches that scholars have adopted to analyze the complexities of media messages about race and ethnicity, from the notion of 'representation' to more recent concepts like Critical Race Theory. Second, the book reviews studies related to a variety of media, including film, television, print media, social media, music, and video games. Finally, contributors present a broad summary of media issues related to specific races and ethnicities and describe the relationship of the study of race to the study of gender and sexuality"–Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

Independent Videogames: Cultures, Networks, Techniques And Politics - Ruffino, Paolo (Routledge, 2021)
Independent Videogames investigates the social and cultural implications of contemporary forms of independent video game development. Through a series of case studies and theoretical investigations, it evaluates the significance of such a multi-faceted phenomenon within video game and digital cultures. A diverse team of scholars highlight the specificities of independence within the industry and the culture of digital gaming through case studies and theoretical questions. The chapters focus on labor, gender, distribution models and technologies of production to map the current state of research on independent game development. The authors also identify how the boundaries of independence are becoming opaque in the contemporary game industry – often at the cost of the claims of autonomy, freedom and emancipation that underlie the indie scene. The book ultimately imagines new and better narratives for a less exploitative and more inclusive videogame industry. Systematically mapping the current directions of a phenomenon that is becoming increasingly difficult to define and limit, this book will be a crucial resource for scholars and students of game studies, media history, media industries and independent gaming.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

War Games: Memory, Militarism and the Subject of Play - Hammond, Philip; Pötzsch, Holger (Bloomsbury Publishing USA, 2019)
Many of today's most commercially successful videogames, from Call of Duty to Company of Heroes, are war-themed titles that play out in what are framed as authentic real-world settings inspired by recent news headlines or drawn from history. While such games are marketed as authentic representations of war, they often provide a selective form of realism that eschews problematic, yet salient aspects of war. In addition, changes in the way Western states wage and frame actual wars makes contemporary conflicts increasingly resemble videogames when perceived from the vantage point of Western audiences.This interdisciplinary volume brings together scholars from games studies, media and cultural studies, politics and international relations, and related fields to examine the complex relationships between military-themed videogames and real-world conflict, and to consider how videogames might deal with history, memory, and conflict in alternative ways. It asks: What is the role of videogames in the formation and negotiation of cultural memory of past wars? How do game narratives and designs position the gaming subject in relation to history, war and militarism? And how far do critical, anti-war/peace games offer an alternative or challenge to mainstream commercial titles?
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Video Games Have Always Been Queer. - Ruberg, Bonnie (New York University Press, 2019)
While popular discussions about queerness in video games often focus on big-name, mainstream games that feature LGBTQ characters, like 'Mass Effect' or 'Dragon Age', Bonnie Ruberg pushes the concept of queerness in games beyond a matter of representation, exploring how video games can be played, interpreted, and designed queerly, whether or not they include overtly LGBTQ content. 'Video Games Have Always Been Queer' argues that the medium of video games itself can-and should-be read queerly. In the first book dedicated to bridging game studies and queer theory, Ruberg resists the common, reductive narrative that games are only now becoming more diverse. Revealing what reading D.A. Miller can bring to the popular 2007 video game 'Portal', or what Eve Sedgwick offers 'Pong', Ruberg models the ways game worlds offer players the opportunity to explore queer experience, affect, and desire. As players attempt to 'pass' in 'Octodad' or explore the pleasure of failure in 'Burnout: Revenge', Ruberg asserts that, even within a dominant gaming culture that has proved to be openly hostile to those perceived as different, queer people have always belonged in video games-because video games have, in fact, always been queer.
OCLC: 1099909377
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; _Nettoyé

Virtual History: How Videogames Portray the Past - Wainwright, A. Martin (Routledge, 2019)
Virtual History examines many of the most popular historical video games released over the last decade and explores their portrayal of history. The book looks at the motives and perspectives of game designers and marketers, as well as the societal expectations addressed, through contingency and determinism, economics, the environment, culture, ethnicity, gender, and violence. Approaching videogames as a compelling art form that can simultaneously inform and mislead, the book considers the historical accuracy of videogames, while also exploring how they depict the underlying processes of history and highlighting their strengths as tools for understanding history. The first survey of the historical content and approach of popular videogames designed with students in mind, it argues that games can depict history and engage players with it in a useful way, encouraging the reader to consider the games they play from a different perspective. Supported by examples and screenshots that contextualize the discussion, Virtual History is a useful resource for students of media and world history as well as those focusing on the portrayal of history through the medium of videogames.
Google-Books-ID: RZqfDwAAQBAJ
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Settler Colonialism in the Digital Age: Clash of Clans, Territoriality, and the Erasure of the Native - Euteneuer, Jacob (Open Library of Humanities, 2018)
In the past ten years, two seemingly unconnected fields of study have risen to prominence. Patrick Wolfe’s 2006 theorization of settler colonialism called for the development of a distinct set of literature and analytical tools to analyze the relationship between indigenous peoples and occupying settlers. Meanwhile, Ian Bogost’s 2007 elaboration of the notion of procedural rhetoric provided a theoretical framework to approach the critical analysis of the ideology modeled by a game’s rules and design. While each of these theories have proliferated and prospered within their disciplines, this article seeks to bring the two fields together in order to establish a critical framework that can be used to highlight the presence of settler colonialism in popular mobile videogames, in particular Supercell’s 2012 mobile game Clash of Clans. Within this framework, the essay analyzes how the game engages in a system of play driven by its focus on improvement, progression, and expansion, which ends up operating under the same principles settler colonialism has used to justify the expansion of settler-states and the eradication of indigenous populations. Through an examination of the game’s economy, enemies, maps, and music, the essay connects the game’s systems of play to the embedded nature of settler colonialism in the videogame industry—particularly the mobile or casual scene—and contemporary life in settler-states. The ultimate goal is to explain how social meaning is derived from these types of games and what that means for both players and creators in terms of developing new, progressive opportunities for play.
Number: 1
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Queerness in Play - Harper, Todd; Adams, Meghan Blythe; Taylor, Nicholas (Palgrave Macmillan, 2018)
"Queerness in Play examines the many ways queerness of all kinds - from queer as 'LGBT' to other, less well-covered aspects of the queer spectrum - intersects with games and the social contexts of play. The current unprecedented visibility of queer creators and content comes at a high tide of resistance to the inclusion of those outside a long-imagined cisgender, heterosexual, white male norm. By critically engaging the ways games - as a culture, an industry, and a medium - help reproduce limiting binary formations of gender and sexuality, Queerness in Play contributes to the growing body of scholarship promoting more inclusive understandings of identity, sexuality, and games."–Provided by publisher.
OCLC: 1057550232
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Gaming Representation: Race, Gender, and Sexuality in Video Games - Malkowski, Jennifer; Russworm, TreaAndrea M. (Indiana University Press, 2017)
Gaming Representation' offers a timely and interdisciplinary call for greater inclusivity in video games. The issue of equality transcends the current focus in the field of Game Studies on code, materiality, and platforms. Journalists and bloggers have begun to hold the digital game industry and culture accountable for the discrimination routinely endured by female gamers, queer gamers, and gamers of color. Video game developers are responding to these critiques, but scholarly discussion of representation in games has lagged behind. Contributors to this volume examine portrayals of race, gender, and sexuality in a range of games, from casuals like Diner Dash, to indies like Journey and The Binding of Isaac, to mainstream games from the Grand Theft Auto, BioShock, Spec Ops, The Last of Us, and Max Payne franchises. Arguing that representation and identity function as systems in games that share a stronger connection to code and platforms than it may first appear, 'Gaming Representation' pushes gaming scholarship to new levels of inquiry, theorizing, and imagination.
Google-Books-ID: qJwRvgAACAAJ
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créatrice; _Nettoyé

Queer Game Studies - Ruberg, Bonnie; Shaw, Adrienne (University of Minnesota Press, 2017)
The in-depth, diverse, and accessible essays in Queer Game Studies use queerness to challenge the ideas that have dominated gaming discussions. This volume reveals the capacious albeit underappreciated communities that are making, playing, and studying queer games, demonstrating the centrality of LGBTQ issues to the gamer world and establishing an alternative lens for examining this increasingly important culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

Gaming at the Edge: Sexuality and Gender at the Margins of Gamer Culture - Shaw, Adrienne (University of Minnesota Press, 2015)
Video games have long been seen as the exclusive territory of young, heterosexual white males. In a media landscape dominated by such gamers, players who do not fit this mold, including women, people of color, and LGBT people, are often brutalized in forums and in public channels in online play. Discussion of representation of such groups in games has frequently been limited and cursory. In contrast, Gaming at the Edge builds on feminist, queer, and postcolonial theories of identity and draws on qualitative audience research methods to make sense of how representation comes to matter. In Gaming at the Edge, Adrienne Shaw argues that video game players experience race, gender, and sexuality concurrently. She asks: How do players identify with characters? How do they separate identification and interactivity? What is the role of fantasy in representation? What is the importance of understanding market logic? In addressing these questions Shaw reveals how representation comes to matter to participants and offers a perceptive consideration of the high stakes in politics of representation debates. Putting forth a framework for talking about representation, difference, and diversity in an era in which user-generated content, individualized media consumption, and the blurring of producer/consumer roles has lessened the utility of traditional models of media representation analysis, Shaw finds new insight on the edge of media consumption with the invisible, marginalized gamers who are surprising in both their numbers and their influence in mainstream gamer culture.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Avatars of Whiteness: Racial Expression in Video Game Characters - Dietrich, David R. (Sociological Inquiry, 2013)
Video games are an enormous segment of popular media today, comparable to tele-vision and movies. Moreover, video games represent a new form of media distinguishedfrom previous forms due to the interactive element, where game players have the ability to change and influence the game world. This paper contributes to the study of race and popular media by examining how race is presented in role-playing video games throughthe feature of avatar creation. Capabilities for avatar creation are analyzed in over sixty massively multiplayer online role-playing games (MMORPGs) in service as of early2010 and twenty offline role-playing games (RPGs) published over the past 10 years.The analysis shows that the vast majority of games, both online and offline, do not allow for the creation of avatars with a non-white racial appearance. Forcing an Angloappearance on avatars that purport to represent the player has the potential to reinforce asense of normative whiteness as well as shape the social composition of online worldsinto all-white virtual spaces, contributing to the creation of a virtual“white habitus.”
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Palgrave Macmillan, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Section: xi, 279 p. : ill. ; 23 cm.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play – the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Google-Books-ID: jXjHAgAAQBAJ
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

What's in a Game? Race, Gender, and LGB Representation in Video Games - Wilberg, Heather (Roosevelt University, 2011)
Though research examining violence in video games (VGs) and its potential real-world effects has been a target of academic attention, content analysis of demographical marginalization in VGs has not been as prolific. What little research there is reveals a pronounced absence and stereotyping of women and racial or ethnic minorities but ignores queer content altogether. This work explores video game demographics through quantitative analysis of the demographic composition and stereotyping of characters from 30 popular VG titles. Findings of this study support that of past analyses, evidencing that the representation of women and racial minorities is both rare and stereotyped. Queer characters are also shown to be sparse and stereotyped. While past research has largely treated race and gender separately, this study shows that multiply marginalized groups, including queers, are even more underrepresented and stereotyped. The sociocultural implications of these findings are discussed and suggestions are made for future analysis and marketing.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé